2013
DOI: 10.1007/s00405-013-2835-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of the Er-Yag laser used in stapes surgery

Abstract: Stapes surgery is performed using both conventional techniques and a variety of laser systems. The Er-Yag laser is a type of pulsation laser deemed by many to be the safest for ear surgery. The aim of this study was to assess the long-term effects of using the Er-Yag laser in stapes surgery and its impact on inner ear function. The study was conducted on 95 ears (48 right and 47 left) that had undergone Er-Yag laser-assisted stapedotomy. The follow-up time was at least 3 years. Pure tone audiometry was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…Although 30 mJ equates the recommended pulse energy by Szyfter et al ( 31 ) and Hausler et al ( 10 ), results of the perforation were unsatisfactory. In addition, the total energy in all three samples was beyond the recommended total energy of 400 mJ to avoid inner ear damage ( 31 , 32 ). Hence in this study, we cannot conclude that the risk of inner ear damage could be reduced by using 30 mJ pulses.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Although 30 mJ equates the recommended pulse energy by Szyfter et al ( 31 ) and Hausler et al ( 10 ), results of the perforation were unsatisfactory. In addition, the total energy in all three samples was beyond the recommended total energy of 400 mJ to avoid inner ear damage ( 31 , 32 ). Hence in this study, we cannot conclude that the risk of inner ear damage could be reduced by using 30 mJ pulses.…”
Section: Discussionmentioning
confidence: 75%
“…A pulse energy of 60 mJ has been described by Lippert et al ( 30 ) as the optimal energy for footplate perforation. Another set of experiments showed that a single Er:YAG laser shot should not exceed 35 mJ and the total energy should not exceed 400 mJ to avoid inner ear damage ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The usefulness of both CO 2 and Er:YAG lasers in stapes surgery have been confirmed with a decrease in the hearing threshold [11] . The 3-year follow-up of patients who received laser treatment showed that the Er:YAG laser was the safest type of pulsation laser for use in ear surgery because no facial nerve paralysis or adverse effects were observed in the inner ear function [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Такой большой процент неподтверждения тугоухости связан с большим количеством факторов риска, при наличии которых дети направляются на 2-й этап скрининга, что создает повышенную загруженность аудиологической службы и влечет лишние расходы по реализации программы. В связи с этим созрела необходимость пересмотра протокола программы в отношении отслеживания детей c факторами риска [26].…”
unclassified